2001
DOI: 10.1104/pp.010481
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Tomato Xyloglucan Endotransglycosylase Gene That Is Down-Regulated by Auxin in Etiolated Hypocotyls

Abstract: The reorganization of the cellulose-xyloglucan matrix is proposed to serve as an important mechanism in the control of strength and extensibility of the plant primary cell wall. One of the key enzymes associated with xyloglucan metabolism is xyloglucan endotransglycosylase (XET), which catalyzes the endocleavage and religation of xyloglucan molecules. As with other plant species, XETs are encoded by a gene family in tomato (Lycopersicon esculentum cv T5). In a previous study, we demonstrated that the tomato XE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(39 citation statements)
references
References 58 publications
2
36
0
1
Order By: Relevance
“…Previous work indicates that increased IAA content can be coupled to regulation of XTH and the increased deposition of lignin, as was observed in the transgenic lines [63-65]. Catalá et al [65] reported a down-regulation of a tomato XTH gene ( LeXET2 ) by auxin and transgenic tobacco lines overproducing IAA exhibited increased lignin content and altered lignin composition [63]. Sitbon et al [64] suggested that the increased lignin deposition may have resulted from increased peroxidase activity, brought about by increased IAA levels and in the transgenic lines, expression levels of several class III peroxidases changed.…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…Previous work indicates that increased IAA content can be coupled to regulation of XTH and the increased deposition of lignin, as was observed in the transgenic lines [63-65]. Catalá et al [65] reported a down-regulation of a tomato XTH gene ( LeXET2 ) by auxin and transgenic tobacco lines overproducing IAA exhibited increased lignin content and altered lignin composition [63]. Sitbon et al [64] suggested that the increased lignin deposition may have resulted from increased peroxidase activity, brought about by increased IAA levels and in the transgenic lines, expression levels of several class III peroxidases changed.…”
Section: Resultsmentioning
confidence: 83%
“…Auxin, for example, has an effect on cell wall structure and expansion, acting in combination with brassinosteroids, which was the only other hormone-related GO category enriched in the transgenic lines. Previous work indicates that increased IAA content can be coupled to regulation of XTH and the increased deposition of lignin, as was observed in the transgenic lines [63-65]. Catalá et al [65] reported a down-regulation of a tomato XTH gene ( LeXET2 ) by auxin and transgenic tobacco lines overproducing IAA exhibited increased lignin content and altered lignin composition [63].…”
Section: Resultsmentioning
confidence: 98%
“…XTH genes constitute a multigene family encoding proteins involved in cell wall construction and disassembly, with diverse levels of expression in Arabidopsis thaliana [38]. In tomato, two isozymes of XTH (LeXET and LeXET2) with opposite patterns of expression have been detected [39]. LeXET was abundant in the rapid elongation region, whereas LeXET2 was more abundant in the mature/non elongating region.…”
Section: Discussionmentioning
confidence: 99%
“…The corresponding genes have been cloned and expressed in Escherichia coli where the heterologous protein generally appears as inclusion bodies (6,(14)(15)(16). One XET isoenzyme from Arabidopsis has been successfully expressed in insect cells using the baculoviral vectors (17) and an isoenzyme of XET from tomato has been expressed in the methylotrophic yeast, Pichia pastoris (18). However, the enzyme yields in all published cases have been relatively low and no attempts have been made to optimize the enzyme production for enhanced yields.…”
Section: Introductionmentioning
confidence: 98%